Lightweight compression with encryption based on asymmetric numeral systems - Duda, Jarosław; Niemiec, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
Data compression combined with effective encryption is a common requirement of data storage and transmission. Low cost of these operations is often a high priority in order to increase transmission speed and reduce power usage. This requirement is crucial for battery-powered devices with limited resources, such as autonomous remote sensors or implants. Well-known and popular encryption techniques are frequently too expensive.
Keywords: symmetric cryptography; lightweight cryptography; data compression; entropy coding